The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jpedsurg.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of very low birth weight infants with spontaneous intestinal perforation: A retrospective case-matched cohort study

Abstract: Background: Spontaneous intestinal perforation (SIP) is an intestinal complication that occurs in very ill preterms. We investigated whether SIP survivors have worse neurodevelopmental and gastrointestinal outcomes and a poorer quality of life than controls. Methods: A retrospective case-matched cohort study was performed involving infants treated for SIP in a NICU between August 1994 and April 2014. Controls and SIP patients were matched to gestational age, gender, and birth period. Medical records were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In the present study, 26.2% of infants died as a result of this complication, which is consistent with the range of 20-40% previously reported. 6 We identified 3 factors at the time of diagnosis that correlated with an increased risk of death in VLBW infants with GI perforation: portal venous gas on abdominal radiography, metabolic acidosis, and elevated lactate. Insight into the predictive nature of these characteristics might result in better prognostic capabilities, albeit if not altering current treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, 26.2% of infants died as a result of this complication, which is consistent with the range of 20-40% previously reported. 6 We identified 3 factors at the time of diagnosis that correlated with an increased risk of death in VLBW infants with GI perforation: portal venous gas on abdominal radiography, metabolic acidosis, and elevated lactate. Insight into the predictive nature of these characteristics might result in better prognostic capabilities, albeit if not altering current treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, the infant mortality rate among VLBW infants has been reported to be more than 100 times that of infants with birth weights of 2500 g or more. 4,6 This is unsurprising, given that this population has an elevated risk of mortality due to chronic lung disease, infection, gastrointestinal (GI) disease, intraventricular hemorrhage (IVH), and other comorbidities. 5 One complication that can increase the risk of death is GI perforation, which affects approximately 2-3% of the VLBW population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in perinatal and neonatal intensive care have improved the survival of very preterm and extremely preterm infants. Spontaneous intestinal perforation (SIP) is emerging as a leading cause of pneumoperitoneum, with a reported incidence of up to 8% in extremely low birth weight (ELBW <1000 g) and 2%–3% in very low birth weight (VLBW <1500 g) infants 1–3. SIP is often confused with perforation associated with necrotising enterocolitis (NEC), a potentially life-threatening condition in preterm infants with significant mortality and morbidity, including long-term neurodevelopmental impairment 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of previous studies assessing the health burden of SIP are contradictory in this context 6. Some of the studies, including a recent large national database study, have reported a significant association between SIP and adverse neurodevelopmental outcomes and mortality 1 6 7. In contrast, few studies have reported no association between SIP and impaired neurodevelopment 8 9…”
Section: Introductionmentioning
confidence: 99%